The Evaluating Business Strategies for Attracting Foreign Direct Investment in Developing Economies: A Case Study of Nigeria - Owokalu, Olufemi Owokalu; Oguntuase , Taiwo; Surulere, Omosuyi Julius; Alaketu, Akeem Abidemi (African Journal of Stability and Development (AJSD), 2025)
This study evaluated Nigeria’s business strategies for attracting foreign direct investment, based on the aspects of regulatory changes, infrastructure improvement, and institutions. Cross-sectional data from 467 firms were subjected to pooled regression analysis within the context of an ex-post facto comparative research design to examine the hypothesis. Regression analysis established that trade reforms had a positive and statistically significant coefficient of 7.25 (p<0.05), followed by infrastructure development with a statistically significant coefficient of 145.60(p<0.000), while institutional regulatory frameworks had a positive moderate coefficient of 6.85 (p<0.000). However, high corporate leverage negatively influenced investment (β=-4.50, p=0.007), though the results showed that the positive effect of customs integration was insignificant (β=0.85, p=0.382). Following these policies, the Foreign Direct Investment (FDI) inflow into Nigeria was $187 million in 2022 due to policy fluctuation, insecurity and poor infrastructure, while the situation was different in Egypt FDI inflow of $8.5 billion in the same year. This policy analysis also outlined that bureaucratic constraints, foreign exchange challenges, and reliance on foreign exchange earnings and mineral exports prompted dependence on profitable but volatile speculative capital flows, which stood at 68% of the total in 2019. The horizontal FDI include investment plans like Nestlé’s $1.8 billion in agro-processing, where it was also seen that other sectors of the economy had poor linkages with small and medium enterprises. There is the need for systemic changes that foster good governance, policy stability, and infrastructure development involving public-private partnerships for catalytic investment.